High Transmembrane Voltage Raised by Close Contact Initiates Fusion Pore - Bu, Bing; Tian, Zhiqi; Li, Dechang; Ji, Baohua (Frontiers in Molecular Neuroscience, 2016)
Membrane fusion lies at the heart of neuronal communication but the detailed mechanism of a critical step, fusion pore initiation, remains poorly understood. Here, through atomistic molecular dynamics simulations, a transient pore formation induced by a close contact of two apposed bilayers is firstly reported. Such a close contact gives rise to a high local transmembrane voltage that induces the transient pore formation. Through simulations on two apposed bilayers fixed at a series of given distances, the process in which two bilayers approaching to each other under the pulling force from fusion proteins for membrane fusion was mimicked. Of note, this close contact induced fusion pore formation is contrasted with previous reported electroporation under ad hoc applied external electric field or ionic charge in-balance. We show that the transmembrane voltage increases with the decrease of the distance between the bilayers. Below a critical distance, depending on the lipid composition, the local transmembrane voltage can be sufficiently high to induce the transient pores. The size of these pores is approximately 1~2 nm in diameter, which is large enough to allow passing of neurotransmitters. A resealing of the membrane pores resulting from the neutralization of the transmembrane voltage by ions through the pores was then observed. We also found that the membrane tension can either prolong the lifetime of transient pores or cause them to dilate for full collapse. This result provides a possible mechanism for fusion pore formation and regulation of pathway of fusion process.